The Role of UK Communities and Leadership in Tackling Female Genital Mutilation - Minasari, Arofah; Pusparini, Patricia Gita (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
Female Genital Mutilation is the act of removing part or all of a woman's external genitalia, including the act of injuring a woman's genitals without medical reasons. It is estimated that more than 200 million women have undergone Female Genital Mutilation procedures. This is an international problem and concern. The practice of Female Genital Mutilation in England emerged due to the arrival of immigrants who brought this culture. The efforts made by the British government in dealing with Female Genital Mutilation are by enforcing the law in the form of creating anti-Female Genital Mutilation laws and educating the public through campaigns and community empowerment. This research was created to try to see the role of British communities and leadership in dealing with Female Genital Mutilation using comparative feminist political theory and the concept of women's rights. This research will use a qualitative descriptive research methodology. The results of this research are in the form of political policy analysis using four approaches, namely gender; policy; and welfare states, state feminism, policy implementation and making, women's movements. As well as the emergence of obstacles in handling efforts which are influenced by various factors.